Prevalence of some cardiovascular risk factors in two populations in Huaraz (3.100 m above sea level) - López de Guimaraes, Douglas (2007)
Objective: to study the prevalence of some of cardiovascular risk factors (RCF) in high altitude born adults of the district of Huaraz-Ancash (3,100 m above sea level).  Materials and methods: comparative study and cross sectional study in individuals over age 18 living in urban (neighborhood of Bethlehem) and the rural (community of Paquishca) areas of the district of Huaraz. After staged sampling, the sample consisted of 204 people (102 urban and 102 rural). A previously validated survey was applied in August, 2004, evaluating 9 parameters. Results: RCF were found in Huaraz, with a greater prevalence in the urban population (95%) that in the rural one (66,7%). Comparing urban vs. rural populations, the prevalence of arterial hypertension AHT was 18,6% vs. 3,9% rural; hypercolesterolemia 13,7% vs. 2%; high LDL 39,2% vs. 5,9%; low HDL 51% vs. 48%; hyperglycemia 5,9% vs. 2%; obesity 15,7% vs. 2%; smoking 21,6% vs. 5%; alcoholism 12.7% vs. 6.9% and sedentary lifestyle 73,5% vs. 26,5%. Six of the nine RCF studied were more prevalent in the urban population (AHT, hypercolesterolemia, high LDL, obesity, smoking and sedentary lifestyle), with statistically signiﬁcant differences. The accumulated individual prevalence of the RCF was also greater in the urban area.  Conclusions: RCF are present in the adult high altitude population of the district of Huaraz, and they are more prevalent in the urban population than in the rural one.